Neutralizing Dromedary-Derived Nanobodies Against BotI-Like Toxin From the Most Hazardous Scorpion Venom in the Middle East and North Africa Region - Ben Abderrazek, Rahma; Ksouri, Ayoub; Idoudi, Faten; Dhaouadi, Sayda; Hamdi, Emna; Vincke, Cécile; Farah, Azer; Benlasfar, Zakaria; Majdoub, Hafedh; El Ayeb, Mohamed; Muyldermans, Serge; Bouhaouala-Zahar, Balkiss (Frontiers in Immunology, 2022)
Scorpion envenoming is a severe health problem in many regions causing significant clinical toxic effects and fatalities. In the Middle East/North Africa (MENA) region, Buthidae scorpion stings are responsible of devastating toxic outcomes in human. The only available specific immunotherapeutic treatment is based on IgG fragments of animal origin. To overcome the limitations of classical immunotherapy, we have demonstrated the in vivo efficacy of NbF12-10 bispecific Nanobody at preclinical level. Nanobodies were developed against BotI analogues belonging to a distinct structural and antigenic group of scorpion toxins, occurring in the MENA region. From Buthus occitanus tunetanus venom, BotI-like toxin was purified and used for dromedary immunization. The 41 N-terminal amino acid residues were sequenced and the LD50 estimated at 40 ng/mouse. An immune VHH library was constructed and after screening two Nanobodies were selected with sub-nanomolar affinity and recognizing an overlapping epitope. NbBotI-01 was able to neutralize 50% of the lethal effect of 13 LD50 BotI-like, in mice when injected by i.c.v route whereas NbBotI-17 neutralized 50% of the lethal effect of 7 LD50. Interestingly, NbBotI-01 completely reduced the lethal effect of the 2 LD50 of BotG50 when injected at 1:4 molar ratio excess. More interestingly, an equimolar mixture of NbBotI-01 with NbF12-10 neutralized completely the lethal effect of 7 and 5 LD50 of BotG50 or AahG50, at 1:4 and 1:2 molar ratio, respectively. Hence, NbBotI-01 and NbF12-10 display synergic effects leading to a novel therapeutic candidate for treating Buthus occitanus scorpion stings in the MENA region.